Cultivation of the microalga Eustigmatos magnus in different photobioreactor geometries and subsequent anaerobic digestion of pre-treated biomass. (September 2019) - Gruber-Brunhumer, M.R.; Schöberl, A.; Zohar, E.; Koenigsberger, S.; Bochmann, G.; Uher, B.; Lang, I.; Schagerl, M.; Fuchs, W.; Drosg, B.
Abstract: Microalgal biomass as a feedstock for biogas production is linked to the parameters biomass productivity and biogas yield. Besides an easy-to-use strain for anaerobic digestion, the photobioreactor (PBR) design is important. A microalgae strain selection revealed Eustigmatos magnus (SAG 36.89) as the most promising strain yielding an average of 100 mg total suspended solids (TSS) L −1 day −1 . The strain was tested in cost-effective sleevebag-PBR-systems of 10 cm, 20 cm and 30 cm diameter facing the light from the front or laterally. Highest mean productivity on a volumetric basis was measured in PBRs with the lowest diameter (104 and 117 mg L −1 day −1 . The highest productivity per m −2 was achieved in 10 cm PBRs with front light configuration (9.35 g TSS m −2 day −1 ). The lateral light configuration of 10 cm PBRs had positive aspects such as the lowest mean water demand to produce 1 kg TSS (481 L −1  kg −1 ) and the lowest mean energy demand for medium separation of 1 kg TSS (106 Wh). The concentrated microalgal biomass was then subjected to ultrasonication and thermal pre-treatment (90 °C and 120 °C) and tested in BMP tests. Mesophilic anaerobic mono-digestion of untreated microalgae biomass led to a methane (CH4 ) yield of 343 L −1  kg −1 volatile solids (VS). Thermal pre-treatment at 120 °C resulted in significantly increased CH4 yields of 430 L −1  kg −1  VS. As thermal pre-treatment can be easily installed nearby a biogas plant it could be an interesting option for AD of microalgal biomass with only little investment. Graphical abstract: Image 1 Highlights: Screening tests proved Eustigmatos magnus a promising strain in anaerobic digestion. 10 cm diameters had highest productivities in cost-saving sleevebag photobioreactors. Lowest water demand and energy consumption for harvest in 10 cm photobioreactors. No differences were observed regarding the direction of light supply. Thermal pre-treatment at 120 °C of E. magnus significantly improved methane yields.